The Influence of Principal Supervision and Motivation on Teacher Performance at MTS Muhammadiyah Garut - Paturahman, Maman; aryanti, Ade Siti H; Samosir, Astuti; Rejeki, Suyekti Kinanthi; Ramadhan, Hanif Bintang (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The success of education as a system in schools is determined by many factors, and one of them is teacher performance. It plays a strategic role in the overall education and learning process at school. Teacher performance is understood as the work performance and appearance of teachers in carrying out their profession professionally and effectively to produce quality graduates. Many factors can influence teacher performance in schools, two of which are educational supervision and strong motivation. The aim of this research is to describe the influence of principal supervision and motivation on teacher performance at MTS Muhammadiyah Garut. The research method used in this study is the survey method with correlational analysis. This means that data is collected with the help of questionnaires. In this study, the instrument used to gather data on the three variables being researched was a questionnaire. Based on the data analysis results, it is concluded that: 1) The results of the hypothesis test show that there is a significant positive relationship between the independent variables of school principal supervision (X1) and motivation (X2) and the dependent variable of teacher performance (Y) with a correlation coefficient of 0.874. The multiple regression relationship is linear with the equation model Y = -44.596 + 1.021 X1 + 0.606 X2; 2) The independent variables of school principal supervision (X1) and motivation (X2), both individually and together, make a significant contribution to the dependent variable of teacher performance (Y). The contribution of each independent variable to the dependent variable is as follows: school principal supervision variable is 67.8% and motivation variable is 48.8%. The contribution of both independent variables together to the dependent variable is 76.4%. Knowing that the contribution of school principal supervision (X1) and motivation (X2), 76.4%, to the performance of the teacher (Y), it can be concluded that 23.6% of the performance of the teacher is due to other factors